Improving participation of hard-to-reach older people in diet interventions: the INVITE strategy. (13th November 2019) - Bocquier, A; Dubois, C; Verger, P; Darmon, N; ,
Abstract: Background: A lot of behavioural interventions promoting healthy eating and physical activity are focusing older people, but, among them, individuals from low socioeconomic status and/or experiencing social isolation participate less. The aim of the present study was to design, pilot and perform a formative evaluation of an active recruitment strategy called 'INVITE'. This strategy aimed to improve participation of hard-to-reach older people in existing collective workshops combining diet and physical activities dedicated to older people. Methods: We co-constructed this strategy, based on results from a literature review, qualitative interviews with older people and professionals using the Behaviour Change Wheel framework as a guide. INVITE includes 5 steps: i) identification of socially deprived/isolated people aged 60-85 years in retirement fund databases; ii) postal invitation letter; iii) phone call; iv) home visit by a social worker. The formative evaluation used questionnaires (closed and open-ended questions) completed by 2 social workers in April 2019. Results: Among the 54 older people selected in the databases, 29 could be reached by phone. Among these 29 persons, 25 reported being interested by the collective workshops; 17 refused the home visit (main reasons: not available during the workshops period, current health problems); 12 accepted the home visit, but only 10 could be visited at home (one was ill; one cancelled the visit). Nine out of these 10 persons accepted to participate to the workshops. The main motivating factors were that workshops were: free; perceived as friendly; and as an opportunity to "go out" and to receive diet counselling to improve diet quality with no additional cost. Conclusions: The INVITE strategy was perceived positively but adjustments are needed to improve home visits acceptation rate (e.g., by revising the criteria used to identify people in the databases). We will now evaluate the attendance rate to the collective workshop. Key messages: The INVITE strategy was designed to improve participation of hard-to-reach older people in combined diet and physical activity collective workshops. This strategy was perceived positively by most older people contacted and both social workers.